P171 Are the european society of cardiology pulmonary hypertension guideline risk assessment criteria associated with 12-month mortality?. (15th November 2017) - Sharp, C; Grove, A; Augustine, D; Carson, K; Easaw, J; Hall, T; Hudson, B; Robinson, G; Coghlan, G; Mackenzie-Ross, R; Suntharalingam, J
Abstract : Background: The European Society of Cardiology (ESC) guidelines for management of pulmonary hypertension (PAH) advocate comprehensive assessment of patients to determine prognosis and to guide treatment decisions, using a set of risk assessment criteria based on expert advice. These criteria are coded Red (high), Amber (medium) and Green (low). It is unclear whether these criteria are associated with short term survival. Aim: To determine whether red/amber/green risk status according to ESC guidelines is associated with 12 month mortality. Methods: This was a "snapshot" observational study using routinely collected clinical data for patients eligible for targeted drug treatment at a regional centre, under shared care with a national centre. All data available at the latest visit within the study period were collated, including demographics, echocardiogram and right heart catheterisation data. Data are reported as mean/median/count/%. Characteristics of deceased and surviving patients were compared using Mann-Witney U-test. Association with 12 month mortality was assessed using Receiver Operator Characteristics (ROC) curve analysis. Results: Routinely collected clinic data were available for 104 patients, echocardiograms for 88 and right heart catheter data for 68. 25% were male, mean age 68.2 years. 45.2% had connective tissue disease-associated PAH, 32.7% inoperable chronic thromboembolic PH, 18.3% Idiopathic PAH. 101 were on treatment, of which 35.6% were on monotherapy, 51.0% on dual oral therapy, 9.6% on intravenous treatments. Baseline data are shown in the table . 25% had one red criterion, 14.4% had two and 8.6% had three or more. 19 patients died in the 12 month follow-up period, 6 of whom had no red criteria. Deceased patients were older (p=0.015) and had shorter walking distance (p=0.003). Risk criteria were worse for symptom progression, WHO functional class, walking distance and for the overall number of red criteria. ROC-curve analysis showed that symptom progression (c-statistic 0.695, p=0.048), walking distance (0.748, p=0.012) and the overall number of red flags (0.710, p=0.033) were the only elements associated with 12 month mortality. Conclusions: The ESC risk assessment criteria are associated with 12 month mortality in this cohort when all criteria are collated. Further work in a large cohort is needed to confirm the clinical utility of these criteria.